Cutaneous metastasis of prostate carcinoma treated with electron radiotherapy - Shigeki Arase (IJU Case Reports, 2019)
Introduction Prostate carcinoma is typically diagnosed and treated, and it rarely manifests as cutaneous metastases. We herein report electron radiotherapy for the treatment of cutaneous metastases causing cellulitis, with a durable clinical response achieved. Case presentation A 70‐year‐old male patient with scrotal cutaneous metastasis of prostate carcinoma was undergoing treatment with docetaxel chemotherapy due to recurring cellulitis originating from the scrotum, and his treatment was interrupted. We administered electron radiotherapy to the scrotal cutaneous metastasis lesions, as irradiation was difficult, and obtained a good clinical effect. Subsequently, he continued chemotherapy, and the scrotal lesions remained clear and dry with no recurring cellulitis for 1 year. Conclusion Electron radiotherapy is one of the safe and effective treatment options for controlling cutaneous metastasis of prostate carcinoma.